Functional Cognition in Critically Ill Children: Asserting the Role of Occupational Therapy - Christina M. Dumas; Lenin C. Grajo (Scholarworks @ WMU, 2021)
In this Opinions in the Profession article, we aim to highlight the distinct importance of functional cognition as an assessment and intervention priority in children. In this paper, we use the population of critically-ill children as a specific case example. Functional cognition is the ability of individuals to use and integrate their thinking and processing skills to accomplish desired tasks in their everyday lives in meaningful contexts. We propose three themes through which occupational therapists can assume a more active role in understanding and addressing functional cognition and its impact on occupational performance in critically ill children. Supported by literature, we assert that occupational therapists should: (a) reframe and use the language of functional cognition with a pediatric perspective, (b) use and develop specific assessments to address functional cognition with critically ill children, and (c) include a functional cognition lens during occupation-focused interventions with critically ill children. As the profession of occupational therapy continues to prioritize the practice area of functional cognition, assessment and intervention guidelines will need to be further established and more evidence developed for pediatric specific populations. We urge occupational therapists working with critically ill children to begin to consistently use functional cognition as an essential element in all assessment and intervention planning.